EFFECT OF WORK ENVIRONMENT AND DISCIPLINE OF PRODUCTIVITY OF EMPLOYEES IN. TRAIN INDONESIA (Persero) DIVRE II WEST SUMATRA - Maisarowati, Maisarowati; Utami, SE, MBA, Hayu Yolanda; Amaluis, SE, MM, Dina (Pendidikan Ekonomi, 2014)
ABSTRACT The survival of a company is determined by the human resources support that have high quality and capability. This study aims to analyze: 1) The extent to which the influence of the work environment on the productivity of employees working at PT. Kereta Api Indonesia (Persero) Division II West Sumatra. 2) The extent to which the effects on the productivity of labor discipline employees working at PT. Kereta Api Indonesia (Persero) Division II West Sumatra. 3) The extent to which the influence of the work environment and work discipline to employee productivity PT. Kereta Api Indonesia (Persero) Division II West Sumatra.This type of research is descriptive associative. The population of this study were all employees at PT. Kereta Api Indonesia (Persero) Division II West Sumatra, amounting to 87 people with a total sampling techniques Sampling. Data analysis technique used is multiple linear regression. The results of this study indicate that, (1) the work environment have a significant effect on the productivity of employees working at PT. Kereta Api Indonesia (Persero) Division II West Sumatra. (2) the discipline of work have a significant effect on the productivity of employees working at PT. Kereta Api Indonesia (Persero) Division II West Sumatra. (3) environmental and labor discipline together have a significant effect on the productivity of employees working at PT. Kereta Api Indonesia (Persero) Division II West Sumatra. Based on the research leader of the company must be careful to understand the factors that can affect employee productivity. And in a company leader must first know what you want employees to support the work carried employees so employees can work productively produce, because the work environment and work discipline are considered to have a strong positive influence on employee productivity. And the company has always apply the principles of caring, honesty, sincerity, and professionals who became the core of the success of a company.